Effect of Cr3+ doping on the electrochemical performance of Na3V2(PO4)2F3/C cathode materials for sodium ion battery. (1st January 2023) - Yi, Xiaoli; Luo, Hongyue; Zhou, Yongmao; Feng, Shihao; Wang, Jiexi; Wang, Zhixing; Duan, Jianguo; Wang, Ding; Guo, Huajun; Yan, Guochun
Highlights: A feasible sol-gel method was used to obtain a series of nano-sized Na3 V2-x Crx (PO4 )2 F3 /C materials (x = 0–0.2). The optimized material shows high initial discharge capacity (101.9 mAh g −1 at 10 C) and capacity retention (68.7 % after 1000 cycles). Cr 3+ doping in V and Na sites were explored by Density of states (DOS) and defect formation energy calculation. This work provides a simple and effective strategy to improve electrochemical performance of NVPF. Abstract: Na3 V2 (PO4 )2 F3 is considered as one of the most promising cathode materials for sodium-ion batteries (SIBs). However, the low electronic conductivity of this material severely restricts its electrochemical performance. Herein, Cr-doped Na3 V2 (PO4 )2 F3 /C material was synthesized by a simple sol-gel method, and the effects of Cr 3+ doping on the structure, morphology and electrochemical performance were systematically investigated. The optimized material Na3 V2-x Crx (PO4 )2 F3 /C (x = 0.05) exhibits high initial discharge capacity of 101.9 mAh g −1 at 10 C and keep a capacity retention of 68.7 % after 1000 cycles. The improved electrochemical performance can be attributed to the higher crystallinity, improved intrinsic electronic conductivity and sodium ion diffusion coefficient due to the doped Cr 3+, which accelerates the electron transport and charge transfer rate. The optimized Cr-doped Na3 V2 (PO4 )3 F3 /C material obtained in this work can promote the practical application of Na3 V2 (PO4 )3 F3 cathode. Graphical abstract: Image, graphical abstract